Ethnomathematics Learning to Improve Students' Understanding for Numeracy Concepts - Taruly Tampubolon; Sariayu Sibarani; Zuhri; Efendi; Nina Zakiah; Halim Zaini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The Implemented several types of traditional games in learning mathematics, for example by using congklak media to improve numeracy skills. The application of traditional games helps students learn mathematics learning material more easily. This study aims to integrate congklak games to introduce the concept of arithmetic operations to elementary school students in learning mathematics. This study uses a quantitative approach to the experimental research method. The subjects of this study were students of state elementary school 51 at Bengkalis Regency, Riau Province, Indonesia. Data collection techniques used in this study using test techniques. The research instrument grid used was a test of students' numeracy concept abilities. The resut of this study is finding increasing students' understanding of numeracy concepts students who are given learning to count by applying learning methods that apply ethnomathematics through the congklak game is much better than students who are given learning to count by applying the old way. So it can be stated that the application of Ethnomathematics in Learning can improve Students' Understanding of Numeracy Concepts significantly compared to learning using the usual method.